Risk Assessment of Exposure to Carbon Monoxide in a Residential Area around Tofu Manufacturing - Serlly Frida Drastyana; Sendy Ayu Mitra Uktutias (JURNAL KESEHATAN LINGKUNGAN, 2021)
Introduction: The combustion process during the production of tofu leads to the release of Carbon monoxide (CO). This study aimed to analyze the environmental risks of exposure to CO in people residing near the tofu factories in Sidoarjo, Indonesia. Methods: This was an analytic study using a cross-sectional design. Data were obtained from laboratory experiments, interviews, and observations. Five locations of the tofu manufacturing areas as a research location. Results and Discussion: The average CO concentration in five locations was below the quality standard at 54.50 µg/m3. The hazard identification showed CO could have non-carcinogenic health risks. The respondents near the tofu industry inhaled 5.63 µg/kg/day CO in average. Furthermore, at all of the locations, the CO toxic agents in the air have a rate of RQ > 1. This showed that respondents with 55 kg body weight could be exposed to CO for 8 hours/day or for 312 days/ year. As a result, the exposure to CO is unsafe or likely to result in non-carcinogenic effects on the residents in the next 30 years. Conclusion: CO concentration in all tofu manufacturing areas was below the quality standard and could cause health problems. Residents around the factory are advised to avoid exhaust gas emissions from tofu factories by providing an air exhaust system. The residents also can reduce the exposure by using a mask when outdoor activity.